Ice-nucleating proteins are activated by low temperatures to control the structure of interfacial water - Steven J. Roeters (Nature Portfolio, 2021)
Ice-nucleating proteins promote ice formation at high sub-zero temperatures, but the mechanism is still unclear. The authors investigate a model ice-nucleating protein at the air-water interface using vibrational sum frequency generation spectroscopy and simulations, revealing its reorientation at low temperatures, which increases contact with water molecules and promotes their ordering.